Encyclopedia of polymer science and technology - Kroschwitz, Jacqueline I.; Mark, H. F. (Herman Francis), 1895-1992.; Wiley InterScience (Online service) (New York : Interscience Publishers, 1964)
The online edition of the Encyclopedia of Polymer Science and Technology includes the complete text of the third print edition, plus the classic second edition called the Encyclopedia of Polymer Science and Engineering. It addresses all areas of polymer science. It is updated quarterly with new and substantially revised articles.
Title from home page (viewed Dec. 5, 2005).
Executive editor: Jacqueline I. Kroschwitz.
1st paper ed. edited by Herman F. Mark.
Includes bibliographical references.
Mode of access: World Wide Web.
Keywords: Plastics -- Encyclopedias; Polymers -- Encyclopedias; Polymerization -- Encyclopedias; Electronic reference sources; Electronic encyclopedias